The Impacts of COVID-19 on Social Life of University Students in Kabul, Afghanistan, 2021: A Survey Study (Eurasian Medical Research Periodical, 2022)
By prevalence of new types of viral infections, coronavirus disease (COVID-19), has led the majority of world countries in a critical state. This pandemic affected all of life style and daily activities. Objectives and Methods: The main aim of this survey is assessment of daily activities and social life of Kabul students in duration of self-quarantine. This is a survey study, with 74 students of university in Kabul of Afghanistan sample size, after prepare questionnaire in Google form platform, distributed by social media. Results: The survey shown, daily activities of students like: sleeping and using the social media increased (57.3% and 64.4 %) respectively. The study also shows a significant correlation between online activities and physical activities (P